Experimental Determination and Modeling of the Speciation of Uranium(VI) in Phosphoric Acid Medium. Issue 3 (15th April 2016) - Dartiguelongue, Adrien; Provost, Elise; Chagnes, Alexandre; Cote, Gérard; Fürst, Walter
ABSTRACT: Phosphoric acid solutions with 0 < [H3 PO4 ] < 8 mol · L −1 and 0 < U(VI) < 2 mol · L −1 are studied by Infra Red (IR) spectroscopy and modelized using an equation of state adapted for electrolytes. Modeling of H3 PO4 solutions without uranium, based on a data set combining literature data and original IR measurement, shows that the dimer H5 P2 O8 − has to be considered for H3 PO4 apparent concentration higher than 1 mol · L −1 . When uranium(VI) is present and in the considered concentration range, the results of the data treatment are consistent with the existence of three complexes: UO2 (H2 PO4 ) +, UO2 (H2 PO4 )2, and UO2 (H3 PO4 )(H2 PO4 )2, the last two ones being largely predominant.